Comparison of phosphodiesterase 10A and dopamine transporter levels as markers of disease burden in early Parkinson's disease. Issue 10 (3rd June 2019) - Pagano, Gennaro; Niccolini, Flavia; Wilson, Heather; Yousaf, Tayyabah; Khan, Naheed L.; Martino, Davide; Plisson, Christophe; Gunn, Roger N.; Rabiner, Eugenii A.; Piccini, Paola; Foltynie, Thomas; Politis, Marios
ABSTRACT: Background: Recent work has shown loss of phosphodiesterase 10A levels in middle‐stage and advanced treated patients with PD, which was associated with motor symptom severity. Objectives: To assess phosphodiesterase 10A levels in early PD and compare with loss of dopamine transporter as markers of disease burden. Methods: Seventy‐eight subjects were included in this study (17 early de novo, 15 early l ‐dopa–treated, 24 moderate‐advanced l ‐dopa–treated patients with PD, and 22 healthy controls). All participants underwent [ 11 C]IMA107 PET, [ 11 C]PE2I PET, and 3‐Tesla MRI scan. Results: Early de novo PD patients showed loss of [ 11 C]IMA107 and of [ 11 C]PE2I binding in caudate and putamen ( P < 0.001); early l ‐dopa–treated PD patients showed additional loss of [ 11 C]IMA107 in the caudate ( P < 0.001; annual decline 3.6%) and putamen ( P < 0.001; annual decline 2.8%), but loss of [ 11 C]PE2I only in the putamen ( P < 0.001; annual decline 6.8%). Lower [ 11 C]IMA107 correlated with lower [ 11 C]PE2I in the caudate (rho = 0.51; P < 0.01) and putamen (rho = 0.53; P < 0.01). Longer disease duration correlated with lower [ 11 C]IMA107 in the caudate (rho = –0.72; P < 0.001) and putamen (rho = –0.48; P < 0.01), and with lower [ 11 C]PE2I only in the putamen (rho = –0.65; P < 0.001). Higher burden of motor symptoms correlated with lower [ 11 C]IMA107 in the caudate (rho = –0.42; P < 0.05) and putamen (rho = –0.41; P < 0.05), and with lower [ 11 C]PE2I only in the putamen (rho = –0.69; P < 0.001). Conclusion: Our findings demonstrate loss of phosphodiesterase 10A levels very early in the course of PD and is associated with the gradual and progressive increase of motor symptoms. Phosphodiesterase 10A imaging shows similar potential with dopamine transporter imaging to follow disease progression. © 2019 International Parkinson and Movement Disorder Society